Review on Some Malaysian Traditional Medicinal Plants with Therapeutic Properties - Ali Alsarhan,; Ahed Al-Khatib,; Naznin Sultana,; Mohammed Rafiq Abdul Kadir, (Journal of Basic & Applied Sciences, 2021)
There are many medicinal plants that have been used for thousands of years. These plants can now be found in herbal products and as part of the traditional Malaysian health care system because of their therapeutic efficacy. This paper discusses the use of ten medicinal plants in the traditional medicinal system of Malaysia and related scientific studies on their Pharmaceutical properties, which demonstrate their traditional uses. The plants viewed are Amaranthus spinosus L., Arundina graminifolia (D.Don) Hochr., Callicarpa arborea Roxb., Carica papaya L., Citrus grandis L., Coleus amboinicus Lour., Curcuma domestica Valeton., Psidium guajava L., Garcinia atroviridis Griff. ex T. Anders., and Zingiber officinale Rosc. All the plants mentioned in this paper have therapeutic properties, which explains and validates their uses in traditional medicine.